Euston station redevelopment: Regeneration or gentrification?. (January 2021) - Hickman, Robin; Garcia, Milena Martinez; Arnd, Michel; Peixoto, Luisa Feyo Guimaraes
Abstract: The redevelopment of railways stations and their surrounding neighbourhoods offers many opportunities in terms of regeneration, yet there are also concerns over the potential gentrification of areas and displacement of the existing population and local businesses. The most prominent voice on these issues is typically from the project promoter, reflecting their position of power in the decision-making process, but there are other voices to be understood, including varied views from the local community. This paper uses Q methodology to develop discourses associated with the proposed High Speed Two project and redevelopment of Euston station and the surrounding neighbourhoods. 28 in-depth surveys are used with local residents, local employees, politicians, local government officers and academics, covering attitudes to the proposed Euston redevelopment. The Q method analysis highlights three major discourses: the 'Community Activist', the 'Rail Promoter', and the 'Optimistic Practitioner'. Understanding these different discourses, and their components, is important for decision-makers in ensuring that investment strategies can better reflect the different viewpoints evident in the public domain. Ultimately, this can help to improve the social consequences of transport investment.